Mortality in patients hospitalised for diverticulitis in Sweden—A national population‐based cohort study. Issue 3 (4th May 2021) - Granlund, Johan; Sköldberg, Filip; Hjern, Fredrik; Discacciati, Andrea; Søfteland Sandvei, Marie; Olén, Ola; Schmidt, Peter T.
Abstract: Background: Mortality in diverticulitis patients is poorly documented. Aims: To determine short‐ and long‐term mortality in diverticulitis patients compared to matched disease‐free individuals. Methods: By use of nation‐wide registers, mortality among all individuals with a first‐time hospital admission for diverticulitis 1990‐2010 was compared to a disease‐free cohort, matched for gender and age, with up to 21 years of follow‐up. Hazard ratios (HR) for death within 0‐100 days and 101 days–5 years from admission, respectively, were calculated using Cox regression, adjusting for prior comorbidity and social factors. Separate analyses were performed on diverticulitis treated conservatively and surgically. Results: 83 461 diverticulitis and 812 942 disease‐free individuals were included. Among all diverticulitis patients, mortality within 100 days was four times higher than in disease‐free individuals, HR 4.44 (95% confidence interval 4.26‐4.63), and in surgically treated patients, a HR of 12.13 (11.03‐13.34) was observed. Within 100 days, 11.4% of patients receiving surgical treatment died, compared to 3.2% after conservative treatment. From day 101 to 5 years, the HR was 1.40 (1.32‐1.47) after surgical treatment and 1.08 (1.05‐1.10) after conservative treatment. Relative mortality within 100 days was slightly more pronounced in females than males, whereas in the 101 days–5 years interval, HRs were similar between genders. Conclusions: In patients initially admitted for diverticulitis, survival is significantly reduced, both in the short and the long‐term. This highlights the need of further efforts for prevention and optimised treatment.